Critical review of morphological trait assessment in cycad (Cycadophyta: Cycadales) taxonomy: Importance of consistency and need for standardization - Haynes, Jody L. (Phytotaxa, 2026)
Taxonomic treatments within the Cycadales are largely based on gross morphological traits. Inconsistent trait assessment can adversely affect the understanding of species and relationships among them. It can also have long-lasting and broad-ranging implications in other areas of study. The objective of this review was to critically evaluate and quantify gross morphological trait assessment consistency in cycad taxonomic descriptions. Follow-up objectives were, if necessary, to determine which factors continue to affect trait assessment consistency and develop protocols to improve consistency in future works. Critical comparisons of accepted name protologues, synonym protologues, and emended, revised, and recharacterized taxonomic treatments revealed a surprisingly low level of consistency in the assessment of qualitative and quantitative traits, resulting from such things as inclusion of data from immature and/or juvenile plants, immature leaves, and/or immature/aberrant cones; differential/inadequate understanding of the shape of diagnostic structures and/or the terms used to describe them; and incomplete/inadequate assessment of variability within and/or among populations. Protocols developed herein to improve morphological trait assessment consistency include capturing the full range of variability for every trait assessed, understanding and using established terms to describe and evaluate traits and character states, standardizing terms for key traits and character states, and not including as diagnostic traits that are variable within or among populations of the same species, vegetative data from immature or juvenile plants, or reproductive data from smaller-than-normal or aberrant cones.